2008
DOI: 10.1111/j.1365-2249.2008.03635.x
|View full text |Cite
|
Sign up to set email alerts
|

Live probioticBifidobacterium lactisbacteria inhibit the toxic effects induced by wheat gliadin in epithelial cell culture

Abstract: SummaryWheat gliadin induces severe intestinal symptoms and small-bowel mucosal damage in coeliac disease patients. At present, the only effective treatment for the disease is a strict life-long gluten-free diet. In this study we investigated whether probiotics Lactobacillus fermentum or Bifidobacterium lactis can inhibit the toxic effects of gliadin in intestinal cell culture conditions. The ability of live probiotics to inhibit peptic-tryptic digested gliadin-induced damage to human colon cells Caco-2 was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(115 citation statements)
references
References 33 publications
(40 reference statements)
2
102
1
5
Order By: Relevance
“…It is estimated that gluten contamination of GFDs occurs for 32 to 55% of CD patients (30). Probiotics could play a key role in degrading and/or modifying immunogenic epitope contaminants in gluten-free products during gastrointestinal digestion (25,31). This study demonstrated that 10 strains of probiotic lactobacilli hydrolyze gluten under gastrointestinal conditions.…”
Section: Discussionmentioning
confidence: 82%
“…It is estimated that gluten contamination of GFDs occurs for 32 to 55% of CD patients (30). Probiotics could play a key role in degrading and/or modifying immunogenic epitope contaminants in gluten-free products during gastrointestinal digestion (25,31). This study demonstrated that 10 strains of probiotic lactobacilli hydrolyze gluten under gastrointestinal conditions.…”
Section: Discussionmentioning
confidence: 82%
“…Lindfors and coworkers (47) found that B. lactis exerted a protective effect on epithelial cells against cellular damage induced by gliadin incubation. Furthermore, it was observed that the addition of 10 6 and 10 7 CFU/ml, but not 10 5 CFU/ml, of B. lactis was able to preserve TJ in comparison to epithelial cells maintained in the presence of gliadin alone.…”
Section: Probiotics and CDmentioning
confidence: 99%
“…Moreover, proteolytic activity by probiotic VSL#3 was also found to have an importance during food processing to produce predigested and tolerated gliadins for increasing the palatability of gluten-free products [90]. In addition; Bfdbm lactis was found to inhibit the toxic effects of gliadin in intestinal cell culture conditions [91].…”
Section: Celiac Diseasementioning
confidence: 99%